Clinical profile of children (0-5 years) with rota virus diarrhea - Bhatnagar, Shrish; Srivastva, Geetika (International Journal of Contemporary Pediatrics, 2017)
Background: Rotavirus is a common cause of acute watery diarrhea in under 5 years’ children and it may cause severely dehydrating disease in an unvaccinated child. Methods: A Cross sectional study including children aged 0-5 years presenting with complaints of acute watery diarrhea with or without fever at Department of Paediatrics, Eras Lucknow Medical College and Hospital, Lucknow (Uttar Pradesh). Results: Among 399 patients of acute diarrhea, 385 were discharged and 14 took leave against medical advice. No mortality was reported in this study. Out of 399 patients enrolled 161 (40.4%) were rota virus positive on ELISA assay with mean age 18.65 months. (p=0.028). Rotavirus positivity rate was higher among those having decreased urine (p <0.001), severe dehydration (p <0.001), those with mix/formula feed (89.3%) as compared to those having exclusive breastfeeding (33.3%) in <6 month infants (p <0.001), Only 17.5% of the patients had rotavirus immunization however, the positivity rate among those with rotavirus immunization was only slightly lower (40.0%) as compared to those having incomplete rotavirus immunization (40.4%) (p=0.947). Dehydration rate was significantly higher among cases with incomplete immunization (p <0.001). Conclusions: Severe malnutrition, mix/formula feed and improper hygiene makes the children prone for developing acute rotavirus diarrhea. Children with acute rotavirus diarrhea should be monitored for the development of severe dehydration, decreased urine output and electrolyte derangement especially hypokalemia.